Regional Management of Areas with Indications of Urban Sprawl in the Surrounding Areas of Universitas Muhammadiyah, Yogyakarta, Indonesia - Sri Rum Giyarsih (Indonesian Journal of Geography, 2017)
This research was conducted in the surrounding areas of a university, Universitas Muhammadiyah Yogyakarta (UMY), which is administratively located in Tamantiro Village, Kasihan District, Bantul Regency, the Special Region of Yogyakarta, Indonesia. It aims to formulate the regional management of the surrounding areas as they have been presenting the indications of urban sprawl. It used a qualitative method with research data obtained from in-depth interviews to 22 informants including governmental agencies (7 informants), academics (6 informants), entrepreneurs (5 informants), and villagers (4 informants). The informants were sampled using purposive sampling method. Data processing and analysis were conducted using qualitative descriptive method, i.e. (1) data reduction, (2) data presentation, and (3) data conclusion. Data validation and reliability tests were conducted using source triangulation method. The results show that the stakeholders proposed various management strategies to improve the positive impacts and, at the same time, reduce the negative impacts of urban sprawl. These management strategies include (1) consistency in implementing spatial planning regulation, (2) spatial synergism in development planning, implementation, and monitoring, (3) assistance to the native people and the migrants, and (4) integration between the university and the village.